Role of the Aryl Hydrocarbon Receptor (AhR) in Mediating the Effects of Coffee in the Colon. Issue 20 (31st August 2021) - Chapkin, Robert S.; Davidson, Laurie A.; Park, Hyejin; Jin, Un‐Ho; Fan, Yang‐Yi; Cheng, Yating; Hensel, Martha E.; Landrock, Kerstin K.; Allred, Clinton; Menon, Rani; Klemashevich, Cory; Jayaraman, Arul; et al.
Abstract : Scope: This study investigates the mechanism of action and functional effects of coffee extracts in colonic cells, on intestinal stem cell growth, and inhibition of dextran sodium sulfate (DSS)‐induced intestinal barrier damage in mice. Methods and Results: Aqueous coffee extracts induced Ah receptor (AhR) ‐responsive CYP1A1, CYP1B1, and UGT1A1 gene expression in colon‐derived Caco2 and YAMC cells. Tissue‐specific AhR knockout (AhR f/f x Lgr5‐GFP‐CreERT2 x Villin‐Cre), wild‐type (Lgr5‐CreERT2 x Villin‐Cre) mice are sources of stem cell enriched organoids and both coffee extracts and norharman, an AhR‐active component of these extracts inhibited stem cell growth. Coffee extracts also inhibit DSS‐induced damage to intestinal barrier function and DSS‐induced mucosal inflammatory genes such as IL‐6 and TGF‐β1 in wild‐type (AhR +/+ ) but not AhR –/– mice. In contrast, coffee does not exhibit protective effects in intestinal‐specific AhR knockout mice. Coffee extracts also enhanced overall formation of AhR‐active microbial metabolites. Conclusions: In colon‐derived cells and in the mouse intestine, coffee induced several AhR‐dependent responses including gene expression, inhibition of intestinal stem cell‐enriched organoid growth, and inhibition of DSS‐induced intestinal barrier damage. We conclude that the anti‐inflammatory effects of coffee in the intestine are due, in part, to activation of AhR signaling. Abstract : Summary diagram highlighting the AhR‐dependent effects of coffee extracts in colon cancer cells and the intestine. Coffee extracts induced AhR responsive genes. These same extracts and norharman, an AhR‐active compound in coffee inhibit growth in stem cell enriched organoids and enhanced intestinal barrier function in dextran sodium sulfate‐induced mice. Moreover, effects of coffee extracts on stem cells and barrier function are AhR‐dependent.